Highly Shape-Adaptable Honeycomb Gripper Using Orthotropic Surface Tension - Seo, Yong Sin; Lee, Jae Young; Park, Chanhun; Park, Jongwoo; Han, Byung Kil; Koh, Je Sung; Kim, Uikyum; Rodrigue, Hugo; Bak, Jeongae; Song, Sung Hyuk (IEEE Transactions on Industrial Electronics, 2024)
Astrictive-type grippers, which generate gripping forces from adhesive forces at the contact surface, such as suction cup, are popular end-effectors as picking solutions because of their simplicity and small working space. However, the adhesive force of the astrictive gripper decreases with increasing complexity of the object surface; thus, its application has been restricted to simple picking of objects with a flat surface. Here, in this article, we present an all-round honeycomb astrictive gripper that has an orthotropic surface tension for grasping highly irregular shaped objects with an uneven surface. The design is inspired by mimicking the two-level (macro- and mesoscale) shape adaptation of the octopus's leg. The stiffness-variable structure is also consisted to change its stiffness similar to the function of octopus's leg, and owing to the combination of these structures makes possible to perform various tasks, including hammering, breakfast serving, and vaccination, which were not possible for previous astrictive gripper.
Keywords: Adaptive structure; Adhesive force; Gripping force; Shape-adaptive; Shape-adaptive structure; Soft robotics; Stiffness-variable structure; Suction grippers; Universal gripper; Variable structures; Shape-adaptive structure; soft robotics; stiffness-variable structure; suction gripper; universal gripper